Fatty Acid Composition and Anticancer Activity of Neutral and Polar Lipids of Pacific Oyster ( Crassostrea gigas ) Cultured in Khanh Hoa Coast in Vietnam - Minh Van Nguyen; Derrick Kakooza; Thi Hong Tuoi Do; Anh Phuong Thi Tran; Han The Nguyen; Ngoc Quang Tran (Polish Journal of Food and Nutrition Sciences)
In this study, we investigated the fatty acid composition and anticancer activity of neutral and polar lipid fractions extracted from Crassostrea gigas oysters cultured in Nha Phu Lagoon, Khanh Hoa Coast, harvested during the five months of January, April, May, September, and November. Analysis revealed that saturated fatty acids (SFAs) were the most abundant fatty acids in the neutral lipid fraction, followed by monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs). Conversely, the polar lipid fraction exhibited a different order, with PUFAs being the most abundant, followed by MUFAs and SFAs. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were identified as the most prevalent polyunsaturated fatty acids, while oleic acid and palmitic acid were the predominant monounsaturated and saturated fatty acids, respectively. Notably, the combined content of EPA and DHA in the polar lipid fraction consistently exceeded 30% throughout all five months of analysis. Thrombogenicity index (TI) values ranged from 0.13 to 0.29 for the polar lipid fraction and from 0.6 to 1.1 for the neutral lipid fraction. Moreover, the polar lipid fraction exhibited significantly higher n3/n6 ratios compared to the neutral lipid fraction. The polar lipid fraction exhibited stronger inhibitory effects on the growth of the three cancer cell lines (HepG2, MDA-MB-231, and RD) compared to the neutral lipid fraction. The findings of the present study show that lipids extracted from C. gigas oysters cultured in Khanh Hoa Coast have a weak anticancer activity but may still aid in prevention and treatment of certain cancer types.